Problems and Monitoring in Implementation of Guidance and Counseling Programs at School - Humaira Mustika; Firman Firman; Neviyarni S; Muhammad Asyraf Bin Che Amat (Universitas PGRI SUMATERA BARAT, 2023)
Guidance and counseling supervision aims to provide self-development facilities, and school counselor skills to improve counselor competence and increase responsibility in counseling and create guidance service programs. Found that the purpose of a school supervisor for guidance and counseling can use several approaches including conducting assessments, prevention, motivation, and providing reinforcement to find out the benefits of the program and the implementation of guidance and counseling in schools that have been achieved. and knowing progress and weaknesses, as well as having preventive steps to avoid deviations because prevention is better than repair. The research method is literature study, collecting data by finding sources and constructing them from various sources such as books, journals, and existing research. The results and discussion of the results of the research conducted at the school is that the school principal and the school superintendent are functional officials who serve as technical implementers to supervise the education of certain designated or designated schools.